Future data and security engineering : Third International Conference, FDSE 2016, Can Tho City, Vietnam, November 23-25, 2016, Proceedings /: Third International Conference, FDSE 2016, Can Tho City, Vietnam, November 23-25, 2016, Proceedings. ([2016]) - Unknown
No abstract available